The design, synthesis and evaluation of selenium-containing 4-anilinoquinazoline hybrids as anticancer agents and a study of their mechanism. Issue 25 (14th June 2018) - An, Baijiao; Zhang, Shun; Hu, Jinhui; Pan, Tingting; Huang, Ling; Tang, Johnny Cheuk-on; Li, Xingshu; Chan, Albert S. C.
Abstract : We report the design, synthesis and evaluation of 2-chloro- N -methyl- N -(4-selenocyanatophenyl)quinazolin-4-amine and its analogues as anticancer agents and the mechanism study. Abstract : Inhibition of tubulin polymerization is one of the significant strategies in the treatment of cancer. Inspired by the excellent antitumor activity of EP128495 and the beneficial biological activities of selenium compounds, a series of new selenium-containing 4-anilinoquinazoline hybrids were synthesized and evaluated as tubulin polymerization inhibitors. An anti-proliferative activity assay showed that most of the compounds inhibited human sensitive cancer cells at low nanomolar concentrations. A mechanism study revealed that the optimal compound5a disrupted microtubule dynamics, decreased the mitochondrial membrane potential and arrested HeLa cells in the G2/M phase, finally resulting in cellular apoptosis.